Medical composition

By using medical compositions prepared with polyhydroxy fatty acid ester (PHA) with particle size less than 10,000 nm, the shortcomings of existing hemostatic agents and adhesives in terms of bond strength and biocompatibility are solved, and efficient hemostatic, wound healing and Antibacterial effect.

CN119403579APending Publication Date: 2025-02-07CJ CHEILJEDANG CORP +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202380047976.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-06-29
Filing Date
2023-06-30
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

Existing hemostatic agents or medical adhesives have problems with insufficient bond strength and poor biocompatibility in hemostatic and wound healing, and may cause damage or infection to fragile biological tissues.

Method used

A medical composition has been developed that contains polyhydroxy fatty acid esters (PHA) with a particle size of 10,000 nm or less, which contains 40% or more of 3-hydroxybutyrate (3HB) repeat units and passes specific The preparation method is prepared into particles with excellent biodegradability and biocompatible.

Benefits of technology

The medical composition exhibits high bond strength, can effectively stop bleeding, promote wound healing, and has excellent effects in inhibiting bacterial infection and antibacteriality, and is particularly suitable for fragile biological tissues and humid environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119403579A_ABST
    Figure CN119403579A_ABST
Patent Text Reader

Abstract

The invention relates to a medical composition containing polyhydroxyalkanoate (PHA). The medical composition can exhibit excellent biodegradability, biocompatibility, adhesion to biological tissues, wound healing efficacy and hemostatic efficacy. Therefore, the medical composition according to the present disclosure can be used for hemostasis, wound healing, tissue adhesion, or inhibition of bacterial infection.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a medical composition suitable for human or animal biological tissues and a preparation method thereof. Background Art

[0002] When bleeding occurs due to injuries in daily life or industrial environments, surgical operations are performed to prevent excessive bleeding at the wound site and to perform rapid and safe emergency hemostasis. In such surgical operations, effective hemostasis and suturing of the wound site can reduce the patient's bleeding and blood transfusion, and promote the patient's recovery; therefore, good treatment is necessary.

[0003] Traditionally, medical devices such as gauze, bandages, surgical sutures, staplers or electricity and lasers have been used for hemostasis and suturing treatment. However, when the biological tissue (e.g., skin) of the patient is fragile, their use has the problem of causing side effects such as damage or infection to the wound site.

[0004] To address this problem, hemostatic agents or medical adhesives have been developed. When a hemostatic agent or medical adhesive is applied to a bleeding wound, it exhibits physical, chemical or biologically active properties, primarily to prevent bleeding and help the wound site recover. In addition, since it is applied to the wound site as a coating, it can minimize damage or infection to the wound site even if the patient's biological tissue is fragile.

[0005] However, currently developed hemostatic agents or medical adhesives have limitations in that they do not exhibit the adhesive strength required for suturing wound sites or induce immune responses, resulting in poor biocompatibility.

[0006] [Prior art literature]

[0007] [Patent Literature]

[0008] (Patent Document 1) Korean Patent Publication No. 2013-0055847 Summary of the invention

[0009] Technical issues

[0010] The present disclosure aims to provide a medical composition which minimizes the occurrence of immune response, exhibits high adhesive strength to biological tissues, and is excellent in hemostatic efficacy, wound healing efficacy, bacterial infection inhibition efficacy, and antibacterial efficacy.

[0011] In addition, the present disclosure aims to provide a method for preparing the medical composition.

[0012] Technical Solution

[0013] According to one aspect of the present disclosure, in order to solve the above-mentioned problems, a medical composition is provided, which includes a polyhydroxyalkanoate (PHA) having a particle size of 10,000 nm or less and including a repeating unit derived from 3-hydroxybutyrate (3HB) in an amount of 40 wt % or more based on the total weight.

[0014] In one embodiment, the medical composition may have a tissue adhesion strength of 15 kPa or more when measured at 100% relative humidity and room temperature.

[0015] In another embodiment, the polyhydroxyalkanoate (PHA) may further comprise repeating units derived from 4-hydroxybutyrate (4HB).

[0016] In another embodiment, the repeating unit derived from 4-hydroxybutyrate (4HB) may be included in an amount of 0.1 to 60 wt % based on the total weight of the polyhydroxyalkanoate (PHA).

[0017] In another embodiment, the polyhydroxyalkanoate (PHA) may be a poly(3-hydroxybutyrate-co-4-hydroxybutyrate) copolymer.

[0018] In another embodiment, the molecular weight of the polyhydroxyalkanoate (PHA) may be 10,000 to 1,200,000 g / mole.

[0019] In another embodiment, the polyhydroxyalkanoate (PHA) may be included in the medical composition in a concentration of 0.1 to 75% (w / v).

[0020] In another embodiment, the medical composition can be used to stop bleeding.

[0021] In another embodiment, the medical composition can be used for wound healing.

[0022] In another embodiment, the medical composition can be used for tissue adhesion.

[0023] In another embodiment, the medical composition can be used to inhibit bacterial infection.

[0024] Meanwhile, according to another aspect of the present disclosure, a method for preparing a medical composition is provided, which includes dissolving polyhydroxyalkanoate (PHA) in a solvent to prepare a dispersed phase solution; preparing a continuous phase solution containing a surfactant; passing the dispersed phase solution through a membrane having a pore size of 10,000 nm or less to form an emulsion in which dispersed phase particles are dispersed in the continuous phase solution; and solidifying the emulsion to obtain polyhydroxyalkanoate (PHA) particles having a particle size of 10,000 nm or less.

[0025] In one embodiment, the polyhydroxyalkanoate (PHA) may be included in the dispersed phase solution in an amount of 0.01 to 5 wt % based on the total weight of the dispersed phase solution.

[0026] In another embodiment, the dispersed phase solution may be passed through the membrane at a pressure of 2.5 to 320 kPa.

[0027] According to another aspect of the present disclosure, a method for preparing a medical composition is provided, which includes dissolving polyhydroxyalkanoate (PHA) in a solvent to prepare a dispersed phase solution; preparing a continuous phase solution containing a surfactant; mixing the dispersed phase solution with the continuous phase solution to form a premixed emulsion; injecting the premixed emulsion into a high-pressure dispersion device (microfluidizer) to form an emulsion in which polyhydroxyalkanoate (PHA) particles having a particle size of 10,000 nm or less are dispersed; and solidifying the emulsion to obtain polyhydroxyalkanoate (PHA) particles.

[0028] In one embodiment, the pressure applied to the premix emulsion by the high pressure dispersing device may be from 1 to 30 kpsi.

[0029] Beneficial Effects

[0030] When the medical composition according to the present disclosure includes polyhydroxyalkanoate (PHA) whose particle size is controlled within a specific range, it has excellent biodegradability and biocompatibility (low immunogenicity), and can exhibit strong adhesive strength to biological tissues.

[0031] Therefore, the medical composition according to the present disclosure can be effectively used for hemostasis, healing or suturing of biological tissues of humans or animals. In particular, the medical composition according to the present disclosure exhibits strong adhesive strength even to biological tissues containing moisture (e.g., tissues with a wet surface or tissues in water), and thus when used for hemostasis of wounds in water, it can exhibit excellent hemostatic efficacy.

[0032] In addition, the medical composition according to the present disclosure can be formulated into various forms depending on the properties of the application site of biological tissue. In particular, the medical composition according to the present disclosure comprises polyhydroxyalkanoate (PHA), which can be mass-produced by a microbial system; therefore, it can economically provide a formulated hemostatic agent or medical adhesive. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 and Figure 2 are images (SEM) showing polyhydroxyalkanoate (PHA) particles prepared in Synthesis Examples 1 to 5 and 10 to 15 according to the present disclosure, respectively.

[0034] Figure 3 and Figure 4 Shown are results of analyzing changes in size and particle size distribution of polyhydroxyalkanoate (PHA) particles using a light scattering analysis method in Test Example 2 according to the present disclosure.

[0035] Figure 5 and Figure 6 Shown are the results of measuring the expression levels of inflammatory cytokines (TNF-α and IL-6) in Test Example 3 according to the present disclosure.

[0036] Figure 7 Shown are the results of evaluating the adhesion performance of the medical composition to pig skin under a 100% wet environment in Test Example 4 according to the present disclosure.

[0037] Figure 8 Shown are the results of evaluating the adhesive properties of the medical composition to the hydrogel in Test Example 5 according to the present disclosure.

[0038] Fig. 9 are images confirming changes in the wound site over time in Test Example 6 according to the present disclosure.

[0039] Fig.10 Shown are the results of calculating changes in wound sites using the Image J program in Test Example 6 according to the present disclosure.

[0040] Fig.11 is an image confirming skin tissue and blood vessels at a wound site in Test Example 6 according to the present disclosure.

[0041] Fig.12 and Fig.13 are images confirming changes in the wound site over time in Test Example 7 according to the present disclosure.

[0042] Figures 14 to 18 is a graph showing the results of gene analysis in Test Example 8 according to the present disclosure.

[0043] Fig.19 Shown are the results of evaluating the hemostatic efficacy of the medical composition in Test Example 9 according to the present disclosure.

[0044] Fig. 20 Shown are the results of evaluating the hemostatic efficacy of the medical composition in Test Example 10 according to the present disclosure.

[0045] Fig.21 These are the results of evaluating the efficacy of the medical composition in inhibiting bacterial infection in Test Example 11 according to the present disclosure. DETAILED DESCRIPTION

[0046] Best Mode for Carrying Out the Invention

[0047] Hereinafter, the present disclosure will be described with reference to embodiments.Herein, the present disclosure is not limited to the disclosure given below, but may be modified into various forms as long as the gist of the present invention is not changed.

[0048] In this specification, when it is mentioned that an element is formed, connected or combined on or under another element, it means all cases where one element is formed, connected or combined with another element directly or indirectly through another element. In addition, it should be understood that the standard of the terms above and below each component may vary depending on the direction in which the object is viewed.

[0049] In this specification, the term "comprising" is intended to specify specific properties, regions, steps, processes, elements and / or components. It does not exclude the existence or addition of any other properties, regions, steps, processes, elements and / or components unless there is a specific description to the contrary.

[0050] All numbers and expressions relating to quantities of components, reaction conditions and the like used herein are to be understood as being modified by the term "about" unless otherwise indicated.

[0051] The present disclosure relates to a biocompatible composition comprising biocompatible polymer particles. Specifically, the present disclosure relates to a medical composition that can adhere to biological tissues and exhibit hemostatic effects, wound healing effects, bacterial infection inhibition effects and antibacterial effects on biological tissues, which will be described in detail below.

[0052] Components of medical compositions

[0053] The medical composition according to the embodiment of the present disclosure includes a polyhydroxyalkanoate (PHA) whose particle size is controlled in a specific range. Specifically, the medical composition according to the embodiment of the present disclosure may be a composition in which polyhydroxyalkanoate (PHA) particles having a particle size in a specific range are dispersed in a general solvent or solution.

[0054] The particle size (average particle size) of the polyhydroxyalkanoate (PHA) is 10,000 nm or less. Specifically, the particle size of the polyhydroxyalkanoate (PHA) can be 9,000 nm or less, 8,000 nm or less, 7,000 nm or less, 6,000 nm or less, 5,000 nm or less, 3,000 nm or less, 1,000 nm or less, 700 nm or less, 500 nm or less, 300 nm or less, or 200 nm or less. For example, the polyhydroxyalkanoate (PHA) may have a particle size (average particle size) of 10 to 10,000 nm, 10 to 9,000 nm, 13 to 8,500 nm, 13 to 6,500 nm, 15 to 5,000 nm, 15 to 4,000 nm, 18 to 3,500 nm, 18 to 2,000 nm, 20 to 1,500 nm, 23 to 1,000 nm, 23 to 950 nm, 25 ... In some embodiments, the present invention provides a particle size of 100-200nm, 150-200nm, 200-300nm, 250-200nm, 200-300nm, 200-400nm, 200-500nm, 200-600nm, 200-800nm, 200-400nm, 200-500nm, 200-600nm, 200-800nm, 200-200nm, 200-200nm, 200-200nm, 200-200nm, 200-200nm, 200-200nm, 200-200nm, 200-200nm, 200-200nm, 200-200nm, 200-200nm, 200-200nm, 200-200nm, 200-200nm, 200-200nm, 200-200nm, 200-200nm, 200-200nm, 200-200nm, 200-200nm, 200-200nm, 200-200nm, 200-200nm, 200-200nm, 200-200nm, 200-200nm, 200-200nm, 200-200nm, 200-200nm, 200-200nm, 200-200nm In addition, when the particle size of polyhydroxyalkanoate (PHA) is within the above range, the medical composition according to the present disclosure can effectively penetrate into injured biological tissues (living tissue cells) as nutrients. Therefore, the medical composition according to the present disclosure can have excellent wound healing efficacy.

[0055] The particle size deviation of the polyhydroxyalkanoate (PHA) may be within ±0.1 μm. Specifically, the particle size deviation may be within ±0.09 μm, within ±0.07 μm, within ±0.05 μm, or within ±0.03 μm.

[0056] The particle size and particle size deviation of polyhydroxyalkanoate (PHA) may refer to the values ​​measured using a nanoparticle size analyzer. Specifically, the particle size and particle size deviation of polyhydroxyalkanoate (PHA) may be measured by dynamic light scattering (DLS) at a temperature of 25°C and a measurement angle of 175° using a nanoparticle size analyzer ZetasizerNano ZS (manufacturer: Maven). Here, the value of the peak of the confidence interval of 0.5 obtained by the polydispersity index (PDI) may be defined as the particle size of polyhydroxyalkanoate (PHA).

[0057] The polyhydroxyalkanoate (PHA) may have a polydispersity index (PDI) of 1 or less, specifically, 0.001 to 1, 0.003 to 0.9, 0.005 to 0.8, or 0.005 to 0.6.

[0058] When the particle size deviation and the polydispersity index of the polyhydroxyalkanoate (PHA) are each within the above range, the dispersibility of the polyhydroxyalkanoate (PHA) particles and the processability of the medical composition may be enhanced.

[0059] The polyhydroxyalkanoate (PHA) comprises repeating units (3HB repeating units) derived from 3-hydroxybutyrate (3HB). The content of the 3HB repeating unit can be 40% by weight or more based on the gross weight of the polyhydroxyalkanoate (PHA), specifically, 40 to 99.9% by weight, 42 to 99.5% by weight, 45 to 99% by weight, 46 to 98.5% by weight, 47 to 98% by weight, 48 to 97% by weight, 50 to 96% by weight, 51 to 95% by weight, 52 to 94.5% by weight, 55 to 94% by weight, 60 to 93.5% by weight, 65 to 93% by weight, 70 to 93% by weight, 75 to 92.5% by weight, 80 to 92% by weight, or 82 to 91.5% by weight.

[0060] The polyhydroxyalkanoate (PHA) may further comprise a repeating unit derived from at least one selected from the group consisting of 4-hydroxybutyrate (4HB), 3-hydroxypropionate (3HP), 3-hydroxyhexanoate (3HH), 3-hydroxyvalerate (3HV), 4-hydroxyvalerate (4HV), 5-hydroxyvalerate (5HV) and 6-hydroxyhexanoate (6HH).

[0061] Specifically, the polyhydroxyalkanoate (PHA) may further include a repeating unit derived from 4-hydroxybutyrate (4HB) (4HB repeating unit). When the polyhydroxyalkanoate (PHA) includes the 4HB repeating unit, the biodegradability, biocompatibility, hemostatic efficacy, wound healing efficacy and adhesive properties of the medical composition may be enhanced.

[0062] The 4HB repeating unit may be included in an amount of 0.1 to 60 wt %, specifically, 0.5 to 58 wt %, 1 to 55 wt %, 1.5 to 54 wt %, 2 to 53 wt %, 3 to 52 wt %, 4 to 50 wt %, 5 to 49 wt %, 6 to 48 wt %, 6 to 45 wt %, 6.5 to 40 wt %, 7 to 35 wt %, 7 to 30 wt %, 7.5 to 25 wt %, 8 to 20 wt %, or 8.5 to 18 wt %, based on the total weight of the polyhydroxyalkanoate (PHA).

[0063] Specifically, the polyhydroxyalkanoate (PHA) may be a poly(3-hydroxybutyrate-co-4-hydroxybutyrate) copolymer. Therefore, the biodegradability, biocompatibility, hemostatic efficacy, wound healing efficacy, and adhesive properties of the medical composition may be enhanced.

[0064] Meanwhile, the crystallinity of polyhydroxyalkanoates (PHA) can be adjusted according to the content of 4HB repeating units. It can be divided into semi-crystalline PHA (scPHA) and amorphous PHA (aPHA).

[0065] Specifically, the content of 4HB repeating units of the scPHA may be 0.1 to 30 wt%, 1 to 28 wt%, 3 to 26 wt%, 5 to 25 wt%, 6 to 23 wt%, 8 to 21 wt%, or 10 to 20 wt%. In addition, the content of 4HB repeating units of aPHA may be 15 to 60 wt%, 20 to 58 wt%, 25 to 55 wt%, 35 to 53 wt%, 40 to 50 wt%, 43 to 49 wt%, or 45 to 48 wt%.

[0066] The polyhydroxyalkanoate (PHA) may consist of scPHA alone, aPHA alone, or a mixture thereof.

[0067] The polyhydroxyalkanoate (PHA) may have a crystallinity measured using a differential scanning calorimeter (DSC) of 90% or less, 85% or less, 80% or less, 75% or less, or 70% or less.

[0068] The molecular weight (weight average molecular weight) of the polyhydroxyalkanoate (PHA) may be 10,000 to 1,200,000 g / mol, specifically, 20,000 to 1,100,000 g / mol, 30,000 to 1,000,000 g / mol, 40,000 to 900,000 g / mol, 45,000 to 850,000 g / mol, 50,000 to 800,000 g / mol, In some embodiments, the molecular weight of the polyhydroxyalkanoate (PHA) is 0.000 to 0.000 g / mol, 60,000 to 750,000 g / mol, 70,000 to 700,000 g / mol, 80,000 to 600,000 g / mol, 90,000 to 500,000 g / mol, 100,000 to 400,000 g / mol, 200,000 to 800,000 g / mol, or 300,000 to 700,000 g / mol. When the molecular weight of the polyhydroxyalkanoate (PHA) is within the above range, the adhesion performance of the medical composition to biological tissues can be enhanced.

[0069] The glass transition temperature (T g ) may be -45 to 80°C, -35 to 50°C, -20 to 20°C, or -15 to 0°C. In addition, the crystallization temperature (T c ) may not be measurable, or may be 60 to 120° C., 70 to 115° C., 75 to 110° C., or 80 to 105° C. In addition, the melting temperature (T m ) may not be measurable, or may be 100 to 170°C, 105 to 160°C, 110 to 150°C, or 115 to 140°C.

[0070] The concentration of the polyhydroxyalkanoate (PHA) may be 0.1 to 75% (w / v) (0.1 to 75% by weight based on the total weight of the medical composition). Specifically, the concentration of the polyhydroxyalkanoate (PHA) contained in the medical composition according to the embodiment of the present disclosure may be 0.2 to 70% (w / v), 0.2 to 60% (w / v), 0.2 to 50% (w / v), 0.3 to 40% (w / v), 0.3 to 30% (w / v), 0.3 to 25% (w / v), 0.3 to 16% (w / v), 0.35 to 15.6% (w / v), 0.7 to 13% (w / v), 3 to 11% (w / v), or 6 to 9% (w / v). When the concentration of the polyhydroxyalkanoate (PHA) is within the above range, the hemostatic efficacy, wound healing efficacy and adhesive properties of the medical composition can be significantly enhanced.

[0071] When measured at 100% relative humidity and room temperature (e.g., 20±5°C, specifically 25°C), the tissue adhesion strength of the medical composition comprising polyhydroxyalkanoate (PHA) according to an embodiment of the present disclosure may be 15 kPa or higher. Specifically, the tissue adhesion strength of the medical composition according to an embodiment of the present disclosure may be 15 to 300 kPa, 18 to 200 kPa, 20 to 100 kPa, or 30 to 50 kPa. When the adhesion strength to biological tissue is within the above range, the medical composition can exhibit high adhesion properties not only to biological tissue that does not contain moisture, but also to biological tissue that contains moisture (e.g., tissue with a wet surface or tissue in water).

[0072] The medical composition according to the embodiment of the present disclosure may also include biocompatible polymers and / or adhesive materials other than polyhydroxyalkanoates (PHA). The biocompatible polymers may specifically be catechol, caffeic acid, gallic acid, and tannin; polysaccharide-based polymers such as chitosan, hyaluronic acid, alginic acid, and dextran; or protein-based polymers such as collagen and gelatin. The adhesive material may specifically be protamine, mussel mucin, or squid sucker protein (suckerin).

[0073] In addition, the medical composition according to the embodiment of the present disclosure may further include a known pharmacologically active substance, which may specifically be an analgesic, an anti-inflammatory, an antibacterial or an antifungal agent.

[0074] The medical composition according to the embodiment of the present disclosure may be formulated into various forms. Specifically, the medical composition according to the embodiment of the present disclosure may have a formulation such as powder, liquid, gel or sheet (film).

[0075] Use of medical compositions

[0076] The medical composition according to the embodiment of the present disclosure can be used in various applications. Specifically, the medical composition according to the embodiment of the present disclosure can be used for hemostasis, wound healing, bedsore healing, tissue adhesion or inhibition of bacterial infection, which will be described in detail below.

[0077] Hemostatic composition

[0078] The medical composition according to the embodiment of the present disclosure may be a hemostatic composition comprising polyhydroxyalkanoate (PHA). Polyhydroxyalkanoate (PHA) has low immunogenicity and therefore has excellent biocompatibility and can effectively stop bleeding. Since the hemostatic composition according to the embodiment of the present disclosure comprises such polyhydroxyalkanoate (PHA), it can effectively stop bleeding of injured biological tissue.

[0079] The polyhydroxyalkanoate (PHA) contained in the hemostatic composition according to an embodiment of the present disclosure has substantially the same components and properties as the polyhydroxyalkanoate (PHA) described in the above-mentioned "Components of the Medical Composition".

[0080] Preferably, the polyhydroxyalkanoate (PHA) contained in the hemostatic composition may contain repeating units derived from 4-hydroxybutyrate (4HB) in an amount of 0.1 to 30 wt %, 1 to 28 wt %, 3 to 26 wt %, 5 to 25 wt %, 6 to 23 wt %, or 10 to 20 wt %, based on the total weight of the polyhydroxyalkanoate (PHA), and its molecular weight may be 30,000 to 1,000,000 g / mol, 40,000 to 900,000 g / mol, 45,000 to 850,000 g / mol, or 50,000 to 800,000 g / mol. In addition, the polyhydroxyalkanoate (PHA) contained in the hemostatic composition may be particles having a particle size (average particle size) of 25 to 700 nm, 25 to 600 nm, 25 to 500 nm, 30 to 400 nm, 30 to 300 nm, 50 to 250 nm, 50 to 230 nm, 70 to 220 nm, 100 to 210 nm, 120 to 200 nm, 130 to 190 nm, 140 to 180 nm, or 150 to 180 nm.

[0081] The concentration of the polyhydroxyalkanoate (PHA) contained in the hemostatic composition according to the embodiment of the present disclosure may be 0.1 to 25% (w / v) (based on 0.1 to 25% (w / v) of the total weight of the hemostatic composition), specifically, 0.3 to 16% (w / v), 0.5 to 15% (w / v), 0.7 to 13% (w / v), 1 to 10% (w / v), 2 to 9% (w / v), 3 to 9% (w / v), or 6 to 8% (w / v). When the concentration of the polyhydroxyalkanoate (PHA) is within the above range, the hemostatic efficacy of the hemostatic composition can be significantly enhanced.

[0082] The hemostatic composition according to the embodiment of the present disclosure may include a general solvent or solution that can uniformly disperse polyhydroxyalkanoate (PHA) while being harmless to a living body (human body). The solvent or solution is not particularly limited, but it specifically includes pure water, saline solution or PBS buffer solution.

[0083] Furthermore, the hemostatic composition according to the embodiment of the present disclosure may further optionally include the above-mentioned biocompatible polymer, the above-mentioned adhesive material, and the above-mentioned pharmacologically active substance.

[0084] Wound healing composition

[0085] The medical composition according to the embodiment of the present disclosure may be a wound healing composition comprising the above-mentioned polyhydroxyalkanoate (PHA). Polyhydroxyalkanoate (PHA) is a nutrient that allows injured biological tissue (living tissue cells) to recover quickly, thus playing a role in increasing the recovery speed of injured biological tissue. Since the wound healing composition according to the embodiment of the present disclosure comprises such polyhydroxyalkanoate (PHA), it can effectively perform healing (treatment) of injured biological tissue.

[0086] The polyhydroxyalkanoate (PHA) contained in the wound healing composition according to an embodiment of the present disclosure has substantially the same components and properties as the polyhydroxyalkanoate (PHA) described in the above-mentioned “Components of the medical composition”.

[0087] Preferably, the polyhydroxyalkanoate (PHA) contained in the wound healing composition may contain repeating units derived from 4-hydroxybutyrate (4HB) in an amount of 0.1 to 30 wt %, 1 to 28 wt %, 3 to 26 wt %, 5 to 25 wt %, 6 to 23 wt %, or 10 to 20 wt %, based on the total weight of the polyhydroxyalkanoate (PHA), and its molecular weight may be 30,000 to 1,000,000 g / mol, 40,000 to 900,000 g / mol, 45,000 to 850,000 g / mol, or 50,000 to 800,000 g / mol. In addition, the polyhydroxyalkanoate (PHA) contained in the wound healing composition may be particles having a particle size (average particle size) of 25 to 700 nm, 25 to 600 nm, 25 to 500 nm, 30 to 400 nm, 30 to 300 nm, 50 to 250 nm, 50 to 230 nm, 70 to 220 nm, 100 to 210 nm, 120 to 200 nm, 130 to 190 nm, 140 to 180 nm, or 150 to 180 nm.

[0088] The concentration of the polyhydroxyalkanoate (PHA) contained in the wound healing composition according to the embodiment of the present disclosure can be 0.1 to 25% (w / v) (based on 0.1 to 25% (w / v) of the total weight of the wound healing composition), specifically, 0.3 to 16% (w / v), 0.5 to 15% (w / v), 0.7 to 13% (w / v), 1 to 12% (w / v), 2 to 11% (w / v), 3 to 10% (w / v), 5 to 9% (w / v), or 6 to 8% (w / v). When the concentration of the polyhydroxyalkanoate (PHA) is within the above range, the wound healing efficacy of the wound healing composition can be significantly enhanced.

[0089] The wound healing composition according to the embodiment of the present disclosure may include a general solvent or solution that can uniformly disperse polyhydroxyalkanoate (PHA) while being harmless to a living body (human body). The solvent or solution is not particularly limited, but it specifically includes pure water, saline solution or PBS buffer solution.

[0090] In addition, the wound healing composition according to the embodiments of the present disclosure may further optionally include the above-mentioned biocompatible polymer, the above-mentioned adhesive material, and the above-mentioned pharmacologically active substance.

[0091] Tissue adhesive composition

[0092] The medical composition according to the embodiment of the present disclosure may be a tissue adhesive composition comprising the above-mentioned polyhydroxyalkanoate (PHA). Polyhydroxyalkanoate (PHA) has various functional groups (e.g., OH groups), and therefore, even when applied to wet biological tissue and biological tissue without moisture (e.g., skin tissue), it can firmly combine (adhere) it with other biological tissues. Since the tissue adhesive composition according to the embodiment of the present disclosure comprises such polyhydroxyalkanoate (PHA), it can effectively suture (adhere) injured biological tissues.

[0093] The polyhydroxyalkanoate (PHA) contained in the tissue adhesive composition according to an embodiment of the present disclosure has substantially the same components and properties as the polyhydroxyalkanoate (PHA) described in the above-mentioned "Components of the Medical Composition".

[0094] Preferably, the polyhydroxyalkanoate (PHA) contained in the tissue adhesive composition may include repeating units derived from 4-hydroxybutyrate (4HB) in an amount of 0.1 to 30 wt%, 1 to 28 wt%, 3 to 26 wt%, 4 to 25 wt%, 5 to 23 wt%, 6 to 20 wt%, 7 to 18 wt%, or 8 to 19 wt%, based on the total weight of the polyhydroxyalkanoate (PHA), and its molecular weight may be 100,000 to 1,000,000 g / mol, 150,000 to 900,000 g / mol, 200,000 to 800,000 g / mol, or 300,000 to 700,000 g / mol. In addition, the polyhydroxyalkanoate (PHA) contained in the tissue adhesive composition can be a particle size (average particle size) of 25 to 700 nm, 25 to 650 nm, 25 to 600 nm, 30 to 550 nm, 30 to 500 nm, 50 to 450 nm, 50 to 400 nm, 70 to 350 nm, 100 to 300 nm, 110 to 290 nm, 120 to 280 nm, 130 to 270 nm, or 140 to 260 nm.

[0095] The concentration of the polyhydroxyalkanoate (PHA) contained in the tissue adhesive composition according to the embodiment of the present disclosure can be 0.1 to 25% (w / v) (based on 0.1 to 25% (w / v) of the total weight of the tissue adhesive composition), specifically, 0.3 to 16% (w / v), 0.5 to 15% (w / v), 0.7 to 14% (w / v), 1 to 13% (w / v), 2 to 12% (w / v), 3 to 11% (w / v), 4 to 10% (w / v), or 5 to 10% (w / v). When the concentration of the polyhydroxyalkanoate (PHA) is within the above range, the biological tissue adhesion performance of the tissue adhesive composition can be significantly enhanced.

[0096] When measured at 100% relative humidity and room temperature (e.g., 20±5°C, specifically, 25°C), the tissue (biological tissue) adhesion strength of the tissue adhesive composition according to the embodiment of the present disclosure may be 15 kPa or higher. Specifically, it may be 15 to 300 kPa, 16 to 270 kPa, 17 to 250 kPa, 18 to 200 kPa, 19 to 150 kPa, 20 to 100 kPa, 25 to 80 kPa, 28 to 60 kPa, or 30 to 50 kPa. In addition, the tissue adhesive strength of the tissue adhesive composition according to the embodiment of the present disclosure to the hydrogel may be 1 to 300 J / m 2 Specifically, it can be 2 to 280 J / m 2 , 3 to 250 J / m 2 , 5 to 230 J / m 2 , 6 to 200 J / m 2 , 7 to 180 J / m 2 , 8 to 150 J / m 2 , 9 to 100 J / m 2 , 10 to 80 J / m 2 , 13 to 70 J / m 2 , 15 to 60 J / m 2 , 17 to 50 J / m 2 , or 20 to 45 J / m 2 When the adhesive strength is within the above range, the tissue adhesive composition can exhibit high adhesive properties not only to biological tissues not containing moisture but also to biological tissues containing moisture (eg, tissues having a wet surface or tissues in water).

[0097] The tissue adhesive composition according to the embodiment of the present disclosure may include a general solvent or solution that can uniformly disperse polyhydroxyalkanoate (PHA) while being harmless to a living body. The solvent or solution is not particularly limited, but it specifically includes pure water, saline solution, or PBS buffer solution.

[0098] Furthermore, the tissue adhesive composition according to the embodiments of the present disclosure may optionally further include the above-mentioned biocompatible polymer, the above-mentioned adhesive material, and the above-mentioned pharmacologically active substance.

[0099] Compositions for inhibiting bacterial infection (antibacterial or sterilizing compositions)

[0100] The medical composition according to the embodiment of the present disclosure may be a composition for inhibiting bacterial infection comprising polyhydroxyalkanoate (PHA). Polyhydroxyalkanoate (PHA) may play a role in inhibiting the reproduction and metabolic function of pathogens (e.g., bacteria, etc.). Since the composition for inhibiting bacterial infection according to the embodiment of the present disclosure comprises such polyhydroxyalkanoate (PHA), it may effectively inhibit bacterial infection in injured biological tissues or tissues that have undergone surgery.

[0101] The polyhydroxyalkanoate (PHA) contained in the composition for inhibiting bacterial infection according to an embodiment of the present disclosure has substantially the same components and properties as those of the polyhydroxyalkanoate (PHA) described in the above-mentioned “Components of the medical composition”.

[0102] Preferably, the polyhydroxyalkanoate (PHA) contained in the composition for inhibiting bacterial infection may contain a repeating unit derived from 4-hydroxybutyrate (4HB) in an amount of 0.1 to 30 wt %, 1 to 28 wt %, 3 to 26 wt %, 5 to 25 wt %, 6 to 23 wt %, or 10 to 20 wt %, based on the total weight of the polyhydroxyalkanoate (PHA), and its molecular weight may be 30,000 to 1,000,000 g / mol, 40,000 to 900,000 g / mol, 45,000 to 850,000 g / mol, or 50,000 to 800,000 g / mol. In addition, the polyhydroxyalkanoate (PHA) contained in the composition for inhibiting bacterial infection may be a particle having a particle size (average particle size) of 25 to 700 nm, 25 to 600 nm, 25 to 500 nm, 30 to 400 nm, 30 to 300 nm, 50 to 250 nm, 50 to 230 nm, 70 to 220 nm, 100 to 210 nm, 120 to 200 nm, 130 to 190 nm, 140 to 180 nm, or 150 to 180 nm.

[0103] The concentration of the polyhydroxyalkanoate (PHA) contained in the composition for inhibiting bacterial infection according to the embodiment of the present disclosure can be 0.1 to 75% (w / v) (based on 0.1 to 75% (w / v) of the total weight of the composition for inhibiting bacterial infection), specifically, 5 to 75% (w / v), 10 to 75% (w / v), 15 to 70% (w / v), 20 to 70% (w / v), 25 to 65% (w / v), 30 to 65% (w / v), or 35 to 55% (w / v). When the concentration of the polyhydroxyalkanoate (PHA) is within the above range, the bacterial infection inhibition efficacy of the composition for inhibiting bacterial infection can be significantly enhanced.

[0104] The composition for inhibiting bacterial infection according to an embodiment of the present disclosure may include a general solvent or solution that can uniformly disperse polyhydroxyalkanoate (PHA) while being harmless to a living body (human body). The solvent or solution is not particularly limited, but it specifically includes pure water, saline solution or PBS buffer solution.

[0105] Furthermore, the composition for inhibiting bacterial infection according to an embodiment of the present disclosure may further optionally include the above-mentioned biocompatible polymer, the above-mentioned binding material, and the above-mentioned pharmacologically active substance.

[0106] Method for preparing medical composition

[0107] In the present disclosure, the medical composition may be prepared by a procedure of granulating polyhydroxyalkanoate (PHA) to have a particle size capable of exhibiting optimal biocompatibility.

[0108] Specifically, the method for preparing a medical composition according to an embodiment of the present disclosure includes dissolving polyhydroxyalkanoate (PHA) in a solvent to prepare a dispersed phase solution (S-1); preparing a continuous phase solution containing a surfactant (S-2); passing the dispersed phase solution through a membrane having a pore size of 10,000 nm or less to form an emulsion in which dispersed phase particles are dispersed in the continuous phase solution (S-3); and solidifying the emulsion to obtain polyhydroxyalkanoate (PHA) particles having a particle size of 10,000 nm or less (S-4).

[0109] Step S-1 is a step of dissolving (dispersing) polyhydroxyalkanoate (PHA) as a starting material in a solvent to prepare a dispersed phase solution in which polyhydroxyalkanoate (PHA) is dispersed.

[0110] The polyhydroxyalkanoate (PHA) used as a starting material may be obtained by disrupting the cells of microorganisms using a mechanical method or a physical method, or may be obtained by disrupting the cells of microorganisms using a non-mechanical method or a chemical method.

[0111] The solvent may not be particularly limited as long as it can dissolve polyhydroxyalkanoate (PHA) as a starting material. Specifically, it may be at least one selected from the group consisting of chloroform, ethyl chloride, dichloromethane, dichloroethane, butyl acetate, and trichloroethane.

[0112] Meanwhile, the dissolution of the polyhydroxyalkanoate (PHA) may be performed by stirring at 40 to 50° C. for 45 to 55 hours, so that the polyhydroxyalkanoate (PHA) may be uniformly dissolved in the solvent.

[0113] The dispersed phase solution prepared by this procedure can include 0.01 to 5 weight % of polyhydroxyalkanoate (PHA) as the initial raw material. Specifically, the dispersed phase solution prepared by this procedure can include an amount of 0.02 to 4.5 weight %, 0.05 to 4 weight %, 0.08 to 3.5 weight %, 0.1 to 3 weight %, 0.2 to 2.5 weight %, 0.35 to 2 weight %, 0.4 to 1.5 weight %, 0.5 to 1.3 weight %, 0.6 to 1.2 weight %, 0.7 to 1 weight %, or 0.75 to 0.9 weight % of polyhydroxyalkanoate (PHA). When the content of polyhydroxyalkanoate (PHA) contained in the dispersed phase solution is within the above range, polyhydroxyalkanoate (PHA) particles having a particle size of 10,000nm or less and uniform shape (spherical) can be obtained.

[0114] Step S-2 is a step of preparing a continuous phase solution containing a surfactant (emulsifier). Specifically, the continuous phase solution may contain a surfactant and an aqueous solvent.

[0115] Specifically, the surfactant may be at least one selected from the group consisting of sodium dodecyl sulfate, sodium lauryl sulfate, sodium laureth sulfate, sodium stearate, sodium cocoyl glycinate and perfluorooctane sulfonate.

[0116] The aqueous solvent may be water, distilled water, deionized water, pure water or ultrapure water.

[0117] When preparing the continuous phase solution, the stirring speed may be 1 to 800 rpm, 50 to 600 rpm, or 200 to 500 rpm. When the stirring speed of the continuous phase solution is within the above range, polyhydroxyalkanoate (PHA) particles having uniform nanoscale size may be obtained.

[0118] The step S-2 of preparing the continuous phase solution may be performed simultaneously with the step S-1, or may be performed before or after the step S-1.

[0119] Step S-3 is a step of passing the dispersed phase solution prepared in step S-1 through a membrane having a pore size of 10,000 nm or less to form an emulsion in which dispersed phase particles (PHA dispersed phase particles) are dispersed in the continuous phase solution prepared in step S-2.

[0120] The membrane may be specifically an inorganic porous membrane (eg, Shirasu porous glass (SPG)) having a pore size of 10,000 nm or less, so that the obtained polyhydroxyalkanoate (PHA) particles may have a desired particle size of 10,000 nm or less.

[0121] The pressure when the dispersed phase solution passes through the membrane can be 2.5 to 320 kPa, specifically, 50 to 320 kPa, 100 to 320 kPa, or 200 to 320 kPa. More specifically, the pressure when the dispersed phase solution passes through the membrane can be adjusted according to the size of the hole. The larger the hole, the lower the pressure that can be used. When the pressure is within the above range, polyhydroxyalkanoate (PHA) particles with uniform shape (spherical) can be obtained.

[0122] Step S-4 is a step of curing the emulsion containing dispersed phase particles to obtain polyhydroxyalkanoate (PHA) particles having a particle size of 10,000 nm or less. The curing of the emulsion may refer to removing the solvent used to dissolve the polyhydroxyalkanoate (PHA) in step S-1. The curing of the emulsion may be carried out by natural drying, vacuum drying in an oven, or drying using a rotary evaporator. The curing of the emulsion may produce a product containing polyhydroxyalkanoate (PHA) particles (e.g., an aqueous dispersion dispersed with PHA particles having a particle size of 10,000 nm or less).

[0123] Meanwhile, a method for preparing a medical composition according to another embodiment of the present disclosure includes dissolving polyhydroxyalkanoate (PHA) in a solvent to prepare a dispersed phase solution (S-1'); preparing a continuous phase solution containing a surfactant (S-2'); mixing the dispersed phase solution with the continuous phase solution to form a premixed emulsion (S-3'); injecting the premixed emulsion into a high-pressure dispersion device (microfluidizer) to form an emulsion (S-4') in which polyhydroxyalkanoate (PHA) particles having a particle size of 10,000 nm or less are dispersed; and solidifying the emulsion to obtain polyhydroxyalkanoate (PHA) particles having a particle size of 10,000 nm or less (S-5').

[0124] Each of steps S-1' and S-2' has substantially the same configuration and characteristics as steps S-1 and S-2. Therefore, detailed description thereof will be omitted.

[0125] Step S-3' is a step of mixing the dispersed phase solution prepared in step S-1' with the continuous phase solution prepared in step S-2' to form a premixed emulsion (A).

[0126] A conventional homogenizer may be used for mixing to form the premix emulsion (A). Mixing by a homogenizer may be performed at a stirring speed of 5,000 to 15,000 rpm for 1 to 5 minutes.

[0127] Step S-4' is a step of injecting the premixed emulsion (A) into a high-pressure dispersion device (microfluidizer) to form an emulsion (B) in which polyhydroxyalkanoate (PHA) particles (dispersed phase particles) having a particle size of 10,000 nm or less are dispersed.

[0128] The high-pressure dispersing device (high-pressure dispersing emulsifying device) is a device that applies pressure to the premixed emulsion (A) to break the droplets of the premixed emulsion (A) into smaller fragments. A typical high-pressure dispersing device can be used.

[0129] The pressure applied by the high-pressure dispersing device to the premixed emulsion (A) can be 1 to 30 kpsi. Specifically, it can be 3 to 25 kpsi, 5 to 20 kpsi, or 9 to 15 kpsi. More specifically, the operating pressure of the high-pressure dispersing device can be adjusted according to the content of polyhydroxyalkanoate (PHA) contained in the dispersed phase solution. The higher the content of polyhydroxyalkanoate (PHA), the higher the pressure that can be operated. When the pressure is within the above range, polyhydroxyalkanoate (PHA) particles with uniform shape (spherical) can be obtained.

[0130] Step S-5' is a step of solidifying the emulsion (B) containing polyhydroxyalkanoate (PHA) particles (dispersed phase particles) to obtain polyhydroxyalkanoate (PHA) particles having a particle size of 10,000 nm or less. The solidification of the emulsion (B) may refer to the removal of the solvent used to dissolve the polyhydroxyalkanoate (PHA) in step S-1'. The solidification of the emulsion (B) may be carried out by natural drying, vacuum drying using an oven, or drying using a rotary evaporator. The solidification of the emulsion (B) may produce a product containing polyhydroxyalkanoate (PHA) particles (e.g., an aqueous dispersion dispersed with PHA particles having a particle size of 10,000 nm or less).

[0131] Since the polyhydroxyalkanoate (PHA) particles are prepared by a membrane emulsification method using a membrane or an emulsification method using a high-pressure dispersion device as described above, the present disclosure can provide polyhydroxyalkanoate (PHA) particles having a particle size of 10,000 nm or less and a uniform shape.

[0132] Meanwhile, the polyhydroxyalkanoate (PHA) particles (products containing polyhydroxyalkanoate (PHA) particles) obtained through step S-4 or step S-5' can undergo additional procedures such as sterilization. Thereafter, the polyhydroxyalkanoate (PHA) particles (products containing polyhydroxyalkanoate (PHA) particles) thus obtained can themselves be used as a medical composition according to an embodiment of the present disclosure. In addition, the obtained polyhydroxyalkanoate (PHA) particles can undergo procedures for forming a preparation such as pulverization, liquefaction, gelation, sheet formation (film formation), etc. to be used as a medical composition according to an embodiment of the present disclosure.

[0133] The mode of the present invention

[0134] Hereinafter, the present disclosure will be described in detail with reference to examples, but the scope of the present disclosure is not limited to the examples.

[0135] <Preparation of PHA particles>

[0136] Synthesis Example 1

[0137] PHA particles were prepared by membrane emulsification using a membrane. Specifically, a poly(3-hydroxybutyrate-co-4-hydroxybutyrate) copolymer ([P(3HB-co-4HB)], 4HB repeating unit: 17 wt%, molecular weight: 687,000 g / mol) was dissolved in chloroform to prepare a 10 ml dispersion phase solution (PHA content: 0.4 wt% or less). In addition, 100 ml of a continuous aqueous solution containing 0.3 wt% of sodium dodecyl sulfate as a surfactant was prepared.

[0138] An IMK-40 (MCTech) device using an SPG (Shirasu-porous glass) membrane was used as an emulsification device, and the prepared dispersion phase solution and continuous phase solution were used to induce the formation of an emulsion. In this case, the pore size of the membrane was 300 nm, the pressure through the membrane was controlled at 150 to 320 kPa, and the stirring speed was controlled at 100 to 300 rpm.

[0139] 200 ml of the formed emulsion was poured into a container capable of maintaining an interface height of less than 10 mm, and chloroform was slowly evaporated at room temperature for 48 hours to induce emulsion solidification. As a result, PHA particles with a particle size of 300 nm or less (specifically, an aqueous dispersion containing PHA particles) were obtained.

[0140] Synthesis Examples 2 to 5

[0141] PHA particles (specifically, aqueous dispersions containing PHA particles) were obtained respectively by the same procedure as in Synthesis Example 1, except that a membrane having a pore size of 200 nm (Synthesis Example 2), 1 μm (Synthesis Example 3), 5 μm (Synthesis Example 4) or 10 μm (Synthesis Example 5) was used.

[0142] Synthesis Examples 6 to 9

[0143] PHA particles (specifically, aqueous dispersions containing PHA particles) were respectively obtained by the same procedure as in Synthesis Example 1, except that the composition and molecular weight of the poly(3-hydroxybutyrate-co-4-hydroxybutyrate) copolymer dissolved in chloroform were adjusted as shown in Table 1 below.

[0144] Synthesis Example 10

[0145] PHA particles were prepared by membrane emulsification using a membrane. Specifically, poly(3-hydroxybutyrate-co-4-hydroxybutyrate) copolymer ([P(3HB-co-4HB)], 4HB repeating unit: 8.7 wt%, molecular weight: 390,000 g / mol) was dissolved in chloroform to prepare 10 ml of a dispersed phase solution (PHA content: 1.0 wt% or less). In addition, 100 ml of a continuous aqueous solution containing 0.3 wt% of sodium dodecyl sulfate as a surfactant was prepared.

[0146] An IMK-40 (MCTech) device using an SPG (Shirasu-porous glass) membrane was used as an emulsifying device, and the prepared dispersed phase solution and continuous phase solution were used to induce the formation of an emulsion. In this case, the pore size of the membrane was 300 nm, the pressure through the membrane was controlled at 150 to 320 kPa, and the stirring speed was controlled at 100 to 300 rpm.

[0147] 200 ml of the formed emulsion was poured into a 1-liter round-bottom flask, and chloroform was evaporated at 57° C. and 150 mbar for 4 hours to induce solidification of the emulsion. As a result, PHA particles having a particle size of 300 nm or less (specifically, an aqueous dispersion containing PHA particles) were obtained.

[0148] Synthesis Examples 11 to 14

[0149] PHA particles (specifically, aqueous dispersions containing PHA particles) were obtained respectively by the same procedure as in Synthesis Example 10, except that a membrane having a pore size of 1 μm (Synthesis Example 11), 2 μm (Synthesis Example 12), 5 μm (Synthesis Example 13) or 10 μm (Synthesis Example 14) was used.

[0150] Synthesis Examples 15 to 17

[0151] PHA particles (specifically, aqueous dispersions containing PHA particles) were obtained respectively by the same procedure as in Synthesis Example 10, except that the content (concentration) of the poly(3-hydroxybutyrate-co-4-hydroxybutyrate) copolymer dissolved in chloroform was adjusted as shown in Table 1 below.

[0152] Synthesis Examples 18 to 20

[0153] PHA particles (specifically, aqueous dispersions containing PHA particles) were obtained by the same procedure as in Synthesis Example 11, except that the content (concentration) of the poly(3-hydroxybutyrate-co-4-hydroxybutyrate) copolymer dissolved in chloroform was adjusted as shown in Table 1 below.

[0154] Synthesis Examples 21 to 25

[0155] PHA particles (specifically, aqueous dispersions containing PHA particles) were obtained respectively by the same procedure as in Synthesis Example 10, except that the composition and molecular weight of the poly(3-hydroxybutyrate-co-4-hydroxybutyrate) copolymer dissolved in chloroform were adjusted as shown in Table 1 below.

[0156] Synthesis Example 26

[0157] PHA particles were prepared by an emulsification method using a high-pressure dispersion device. Specifically, poly(3-hydroxybutyrate-co-4-hydroxybutyrate) copolymer ([P(3HB-co-4HB)], 4HB repeating unit: 8.7 wt%, molecular weight: 390,000 g / mol) was dissolved in chloroform to prepare 25 ml of a dispersed phase solution (PHA content: 5 wt%). In addition, 500 ml of a continuous aqueous solution containing 0.3 wt% of sodium dodecyl sulfate as a surfactant was prepared.

[0158] The dispersed phase solution was added to the continuous phase aqueous solution and a homogenizer (IKA T 25 digital, IKA) for 2 minutes to form a premix emulsion.

[0159] Subsequently, the premixed emulsion was fed into a high pressure dispersion device (LM20, Microfluidics) and pressure was applied to induce the formation of a homogenous emulsion. In this case, the pressure was controlled at 10 kpsi.

[0160] 200 ml of the formed emulsion was poured into a 1-liter round-bottom flask, and chloroform was evaporated at 57° C. and 150 mbar for 4 hours to induce solidification of the emulsion. As a result, PHA particles having a particle size of 300 nm or less (specifically, an aqueous dispersion containing PHA particles) were obtained.

[0161] [Table 1]

[0162]

[0163]

[0164] Test Example 1: Observation of PHA particles

[0165] The PHA particles obtained in Synthesis Examples 1 to 5 and Synthesis Examples 10 to 15, respectively, were observed by scanning electron microscopy (SEM). Figure 1 and Figure 2 .

[0166] refer to Figure 1 and Figure 2 , PHA particles were prepared using membrane emulsification method, and PHA particles with uniform size and spherical shape were well prepared.

[0167] Test Example 2: Analysis of PHA particle distribution

[0168] PHA particles were obtained by the same procedure as in Synthesis Example 1, except that the content (concentration) of PHA was adjusted to 0.042 to 0.334 wt % when preparing the dispersed phase solution. The size of the obtained PHA particles and their distribution changes were analyzed using light scattering analysis (Zetasizer NanoZS, Malvern Instruments, UK). Figure 3 shown.

[0169] In addition, PHA particles were obtained by the same procedure as in Synthesis Examples 10 and 11, except that the content (concentration) of PHA was adjusted to 0.1 to 0.8 wt % when preparing the dispersed phase solution. The size of the obtained PHA particles and their distribution changes were analyzed using light scattering analysis (ZetasizerNano ZS, Malvern Instruments, UK). Figure 4 shown.

[0170] refer to Figure 3 When the content of PHA (initial raw material) contained in the dispersed phase solution is in the range of 0.01 to 0.5 wt %, PHA particles with a particle size of 300 nm or less are well prepared. Figure 4 When the content of PHA (initial raw material) contained in the dispersed phase solution is in the range of 0.1 to 1 wt % and when the pore size of the membrane is 0.3 μm, PHA particles with a particle size of 300 nm or less are well prepared.

[0171] Test Example 3: Evaluation of PHA immunogenicity

[0172] The immunogenicity of the semicrystalline PHA of Synthesis Example 1 (scPHA, [P(3HB-co-4HB)] form, repeating unit derived from 4HB: 17 wt %, molecular weight: 687,000 g / mol) and the amorphous PHA of Synthesis Example 9 (aPHA, [P(3HB-co-4HB)] form, repeating unit derived from 4HB: 48 wt %, molecular weight: 800,000 g / mol) were evaluated separately. The results are shown in FIG. Figure 5 and Figure 6 Specifically, Raw 264.7 cells were suspended in DMEM (Dulbecco's modified Eagle's medium) containing 10% FBS (fetal bovine serum) and cultured at 1×10 5 Cells were dispersed in 48-well plates at a concentration of 10 cells / ml and incubated at 37°C in a CO 2 Incubator for 12 days. Then, scPHA or aPHA dissolved (dispersed) in 0.1M PBS buffer (pH 7.4) was treated at concentrations of 10μg / ml, 100μg / ml, 500μg / ml and 1,000μg / ml, respectively, and cultured for 24 hours. The cultured cell culture medium was taken and the content of TNF-α and IL-6 as inflammatory cytokines was measured using an ELISA kit. In this case, LPS (lipopolysaccharide from Escherichia coli O55: B5 (Cat#L2880, Sigma-Aldrich, St. Louis, Missouri, USA)) was used as a positive control, and 0.1M PBS buffer (pH 7.4) (NT) was used as a negative control.

[0173] refer to Figure 5 and Figure 6 , it can be observed that the expression of inflammatory cytokines TNF-α and IL-6 was inhibited by PHA according to the present disclosure (aPHA 10 μg / ml, aPHA 100 μg / ml, aPHA 500 μg / ml, aPHA 1,000 μg / ml, scPHA 10 μg / ml, scPHA 100 μg / ml, and scPHA 1,000 μg / ml). In particular, when aPHA 1,000 μg / ml and scPHA 1,000 μg / ml were compared with LPS treated at the same concentration (positive control), it was confirmed that PHA according to the present disclosure had significantly lower inflammatory cytokine expression than LPS.

[0174] These results support that PHA according to the present disclosure has low immunogenicity and excellent biocompatibility.

[0175] <Preparation of medical composition>

[0176] Example 1

[0177] PHA particles ([P(3HB-co-4HB)], 4HB repeating unit: 17 wt %, molecular weight: 687,000 g / mol) having a particle size of 178 nm were obtained by the same procedure as in Synthesis Example 1, except that the pore size of the membrane was adjusted. The obtained PHA particles were dissolved (dispersed) in a 0.1 M PBS buffer (pH 7.4) at a concentration range of 0.3 to 16% (w / v) to prepare a composition.

[0178] Example 2

[0179] PHA particles ([P(3HB-co-4HB)], 4HB repeating unit: 17 wt %, molecular weight: 687,000 g / mol) having a particle size of 259 nm were obtained by the same procedure as in Synthesis Example 1, except that the pore size of the membrane was adjusted. The obtained PHA particles were dissolved (dispersed) in a 0.1 M PBS buffer (pH 7.4) at a concentration range of 0.3 to 16% (w / v) to prepare a composition.

[0180] Example 3

[0181] PHA particles ([P(3HB-co-4HB)], 4HB repeating unit: 8.7 wt %, molecular weight: 390,000 g / mol) having a particle size of 180 nm were obtained by the same procedure as in Synthesis Example 11, except that the pore size of the membrane was adjusted. The obtained PHA particles were subjected to a procedure of adjusting the concentration to a range of 0.1 to 10% (w / v) to prepare a composition. In this case, the concentration of the PHA particles was adjusted by concentrating with a rotary evaporator or diluting with pure water.

[0182] Example 4

[0183] The composition was prepared by the same procedure as in Example 3, except that PHA particles ([P(3HB-co-4HB)], 4HB repeating unit: 8.7 wt %, molecular weight: 390,000 g / mol) having a particle size of 580 nm were obtained.

[0184] Example 5

[0185] The composition was prepared by the same procedure as in Example 3, except that PHA particles ([P(3HB-co-4HB)], 4HB repeating unit: 8.7 wt %, molecular weight: 390,000 g / mol) having a particle size of 850 nm were obtained.

[0186] Example 6

[0187] The composition was prepared by the same procedure as in Example 3, except that PHA particles ([P(3HB-co-4HB)], 4HB repeating unit: 8.7 wt %, molecular weight: 390,000 g / mol) having a particle size of 4,740 nm were obtained.

[0188] Example 7

[0189] The composition was prepared by the same procedure as in Example 3, except that PHA particles ([P(3HB-co-4HB)], 4HB repeating unit: 8.7 wt %, molecular weight: 390,000 g / mol) having a particle size of 8,190 nm were obtained.

[0190] Comparative Example 1

[0191] Fibrin glue (Green Cross, Korea) was used (FG).

[0192] Test Example 4: Evaluation of Adhesive Properties 1

[0193] The adhesion strength of each composition to biological tissue was evaluated by measuring the shear stress using a universal testing machine (Instron 5544, Norwood, MA, US). Figure 7 As shown. Specifically, pigskin (Stellen Medical, USA) was cut into 10 mm × 10 mm blocks, placed in 0.1 M PBS buffer (pH 7.4), and placed at 37 ° C for 1 hour. Thereafter, the pigskin was adhered to an aluminum rod measuring 10 mm × 100 mm using a quick adhesive (3M). Then, the composition prepared in Examples 1 and 2 and the fibrin glue of Comparative Example 1 were applied to the surface of the pigskin as samples, respectively. Next, an aluminum rod with pigskin to which no sample was applied was stacked on it, and then the two aluminum rods were fixed using a clamp. The two fixed aluminum rods were incubated at 100% relative humidity and room temperature (RT) for 2 hours. Then, the shear stress until the two aluminum rods were completely separated was measured using a 10kN load cell at a crosshead speed of 10 mm / min.

[0194] refer to Figure 7 It can be confirmed that the compositions of Examples 1 and 2 according to the present disclosure exhibit adhesive strength equal to or better than that of the fibrin glue of Comparative Example 1. In particular, when the particle size of the PHA particles was 259 nm and the concentration of the PHA particles was 3 to 16% (w / v), significantly high adhesive strength was exhibited.

[0195] These results support that it is necessary to adjust the particle size of PHA particles to increase the adhesive strength to biological tissues, and that the medical composition (tissue adhesive composition) according to the present disclosure exhibits strong adhesive strength even in a wet environment.

[0196] Test Example 5: Evaluation of Adhesive Properties 2

[0197] The adhesion strength of each composition to biological tissue was evaluated by measuring the shear stress using a universal testing machine (QC-508E, Cometech, Taiwan). Figure 8 As shown. Specifically, 27.6 mg of N, N'-methylenebis (acrylamide) and 4920 mg of potassium persulfate were dissolved in 30 g of deionized water at 4 ° C. Then, 18.528 ml of N, N-dimethylacrylamide and 270 μl of N, N, N', N'-tetramethylethylenediamine were added thereto and then mixed. This solution was placed in a mold with a width of 1.5 mm and cross-linked at 30 ° C for 16 hours to prepare a hydrogel. The prepared hydrogel was cut into a size of 5 mm × 30 mm, and 10 μl of each of the compositions prepared in Examples 3 to 7 was applied as a sample to the surface of the hydrogel with an area of ​​5 mm × 10 mm. Next, two hydrogel blocks coated with the sample were superimposed and placed at room temperature (RT) for 4 hours. After 4 hours, the shear stress until the two hydrogels were completely separated was measured using a 50N load cell at a crosshead speed of 10 mm / min.

[0198] refer to Figure 8 , the smaller the particle size of the PHA particles, the higher the bonding strength. In particular, when the particle size of the PHA particles is 300 nm or less and the concentration of the PHA particles is 3 to 10% (w / v), a significantly high bonding strength is exhibited.

[0199] These results also support that it is necessary to adjust the particle size of PHA particles to increase the adhesive strength to biological tissues, and that the medical composition (tissue adhesive composition) according to the present disclosure exhibits strong adhesive strength even in a wet environment.

[0200] Test Example 6: Evaluation of Wound Recovery 1

[0201] The PHA particles ([P(3HB-co-4HB)], 4HB repeating unit: 17 wt%, molecular weight: 687,000 g / mol) having a particle size of 178 nm obtained in Example 1 were dissolved (dispersed) in 0.1 M PBS buffer (pH 7.4) at a concentration of 7.8% (w / v) to obtain a composition, which was subjected to a wound recovery test. The results are shown in FIG. Figures 9 to 11As shown. Specifically, Sprague Dawley (SD) rats aged 7 weeks or less, matched in sex and age, were prepared, and sterile surgical instruments were prepared. In addition, the composition in which the PHA particles at a concentration of 7.8% (w / v) were dissolved (dispersed) was sterilized with ultraviolet light. Next, the prepared rats were anesthetized using a respiratory anesthesia machine filled with Ifran solution. The back of each anesthetized rat was shaved with a razor, a circular wound area was produced with a biopsy puncher (Kai Medical, Japan) with a diameter of 8 mm, a UV-sterilized composition was applied, and a sterilized waterproof film was affixed to prevent scratches. Thereafter, the wound recovery process was photographed simultaneously for 21 days using a camera, and the wound area was calculated using the ImageJ program. In addition, they were euthanized using carbon dioxide on the 7th and 14th days after the start of the test. The skin tissue around the wound site was cut into a size of 10 mm × 10 mm, fixed in a formalin solution, and then stained with hematoxylin and eosin (H&E) and Masson trichrome (MT). Images of the stained area were observed using a Leica microscope. In this case, no treatment (NT) was used as a negative control group, and fibrin glue (Green Cross, Korea) (FG) was used as a positive control group.

[0202] refer to Fig. 9 and Fig.10 , the medical composition (PHA) according to the present disclosure reduced the wound area in a faster time than the control group.

[0203] refer to Fig.11 (c) (Hematoxylin and eosin (H&E) staining results), when treated with the medical composition (PHA) according to the present disclosure, it was observed that wound healing proceeded quickly and a large number of new blood vessels were generated. These newly generated blood vessels support the generation of temporary granulation tissue, which can deliver nutrients and oxygen to the expanded tissue required to support the healing process while promoting the growth of new tissue. In addition, the angiogenesis process can help remove waste and dead cells from the wound site and accelerate the healing process. At the same time, when treated with the medical composition (PHA) according to the present disclosure, faster re-epithelialization (epidermal repair) occurred compared to the control group. In particular, newly generated epithelial tongue tissue (epithelial tongue) can be observed starting from the third day only in the group treated with the medical composition (PHA) according to the present disclosure.

[0204] refer to Fig.11 (d) (Masson's trichrome (MT) staining results), when treated with the medical composition (PHA) according to the present disclosure, the granulation tissue remodeled into a more mature collagen content structure more quickly.

[0205] These results support that the medical composition (wound healing composition) according to the present disclosure has wound healing efficacy.

[0206] Test Example 7: Evaluation of Wound Recovery 2

[0207] The PHA particles with a particle size of 178 nm obtained in Example 1 ([P(3HB-co-4HB)], 4HB repeating unit: 17 wt %, molecular weight: 687,000 g / mol) and the PHA particles with a particle size of 180 nm obtained in Example 3 ([P(3HB-co-4HB)], 4HB repeating unit: 8.7 wt %, molecular weight: 390,000 g / mol) were dissolved (dispersed) in 0.1 M PBS buffer (pH 7.4) at a concentration of 25% (w / v) to obtain compositions (PHA1 (4HB repeating unit: 17 wt %) and PHA2 (4HB repeating unit: 8.7 wt %)), and each was subjected to a wound recovery test. The results are shown in FIG. Fig.12 and Fig.13 As shown. Specifically, Sprague Dawley (SD) rats were anesthetized with isoflurane, their backs were shaved, and the skin was cut into a size of 1.5 cm long and 3.0 mm deep to produce a narrow skin wound. Next, 10 μl of each of the PHA1 composition and the PHA2 composition were applied to the wound site, and the wound site was fixed for 3 minutes. After 7 days, the rats were euthanized and the skin was cut into a size of 1 cm×2 cm to contain the wound site. Subsequently, the cut skin was fixed in a p-formaldehyde solution (3.7 wt %) and embedded in paraffin, and the skin cross-section was stained with hematoxylin and eosin (H&E). Thereafter, the image of the stained area was observed using a Leica microscope.

[0208] refer to Fig.12 and Fig.13 , the medical compositions according to the present disclosure (PHA1 and PHA2) allowed the wound site to recover cleanly compared to the control group.

[0209] Test Example 8: Evaluation of wound recovery 3 (Differentially expressed gene (DEG) analysis of PHA particles in in vitro cell lines)

[0210] The PHA particles with a particle size of 178 nm obtained in Example 1 ([P(3HB-co-4HB)], 4HB repeating unit: 17 wt%, molecular weight: 687,000 g / mol) and the PHA particles with a particle size of 180 nm obtained in Example 3 ([P(3HB-co-4HB)], 4HB repeating unit: 8.7 wt%, molecular weight: 390,000 g / mol) were dissolved (dispersed) in 0.1 M PBS buffer (pH 7.4) at a concentration of 25% (w / v) to obtain compositions (PHA1 (4HB repeating unit: 17 wt%) and PHA2 (4HB repeating unit: 8.7 wt%)). DEG analysis was performed on these compositions to determine the genes related to human wound healing affected by the PHA particles. The results are shown in FIG. Figures 14 to 18 Specifically, human vascular cell line HMEC01 and human skin fibroblast HDfn were cultured in PRMI 1640 medium containing 10.0 vol% FBS and 1 vol% penicillin-streptomycin (at 37°C and 5% CO 2 In addition, 10 ml of 1.5 × 10 5 The cell suspension was filled with cell culture medium and incubated at 37°C and 5% CO 2 After incubation, the PHA1 composition and the PHA2 composition were added to the cell culture medium and incubated at 37°C and 5% CO. 2 After further incubation, the culture medium was discarded, 1 ml of trizol was added, and the cells were quickly frozen at -70°C, and ROKIT Genomics Co., Ltd. was requested to perform DEG detection analysis to obtain the results.

[0211] refer to Figures 14 to 18 , genes mainly related to angiogenesis and wound healing were overexpressed in the group treated with PHA particles.

[0212] Test Example 9: Evaluation of hemostatic efficacy 1

[0213] The PHA particles ([P(3HB-co-4HB)], 4HB repeating unit: 17 wt%, molecular weight: 687,000 g / mol) with a particle size of 178 nm obtained in Example 1 were dissolved (dispersed) in 0.1 M PBS buffer (pH 7.4) at a concentration of 7.8% (w / v) to obtain a composition, which was tested for hemostatic performance. Fig.19As shown. Specifically, rabbit whole blood containing sodium citrate solution (3.8%) was centrifuged to separate red blood cells (RBC) and platelet-rich plasma (PRP) for hemolysis analysis and plasma coagulation analysis, respectively. Next, the red blood cells (RBC) were washed four times with saline solution, and the red blood cells diluted to 500 μl (1 ml of RBC and 9 ml of saline solution) were added to a microtube containing 100 mg of the composition (PHA composition). In this case, 100 μl of 0.1% Triton (Triton) and 100 μl of PBS were each used as a positive control (PC) group and a negative control (NC) group. 100 μl of fibrin glue was used as a control group. The microtubes were incubated at 37°C for 1 hour and then centrifuged at 3,500 rpm for 10 minutes. Thereafter, the optical density (OD) of the supernatant thus obtained was analyzed at 540 nm using a microplate reader. Hemolysis (%) was calculated according to the following equation 1 (N=3).

[0214] [Equation 1]

[0215] Hemolysis (%) = {(OD sample - OD negative control group) / (OD positive control group - OD negative control group)} × 100

[0216] refer to Fig.19 The medical composition (hemostatic composition) according to the present disclosure has excellent hemostatic effect.

[0217] Test Example 10: Evaluation of hemostatic efficacy 2

[0218] The PHA particles ([P(3HB-co-4HB)], 4HB repeating unit: 17 wt%, molecular weight: 687,000 g / mol) with a particle size of 178 nm obtained in Example 1 were dissolved (dispersed) in 0.1 M PBS buffer (pH 7.4) at concentrations of 1% (w / v), 3% (w / v), 7% (w / v) and 10% (w / v) to obtain compositions, which were tested for hemostatic properties. The results are shown in FIG. Fig. 20 As shown. Specifically, rabbit whole blood containing sodium citrate solution (3.8%) was centrifuged to separate red blood cells (RBC) and platelet-rich plasma (PRP) for hemolysis analysis and plasma coagulation analysis, respectively. Next, 180 μl of plasma was added to a microtube to which each composition (PHA composition) prepared at the corresponding concentration and 20 μl of nanoparticle suspended silica had been added. Thereafter, the microtube was incubated at 37°C for 30 minutes and then centrifuged at 6,000 rpm for 5 minutes. Next, 100 μl of each supernatant was transferred to one well of a 96-well flat-bottom plate and washed with 65 μl of 50 mM CaCl 2The solution was recalcified. The extent of fibrin polymerization was then assessed by measuring the absorbance at 405 nm every 50 seconds over 1 hour using a plate reader.

[0219] refer to Fig. 20 , the degree of fibrin polymerization of the medical composition (hemostatic composition) according to the present disclosure is high, indicating excellent hemostatic efficacy.

[0220] Test Example 11: Evaluation of efficacy in inhibiting bacterial infection

[0221] The PHA particles with a particle size of 178 nm obtained in Example 1 ([P(3HB-co-4HB)], 4HB repeating unit: 17 wt %, molecular weight: 687,000 g / mol) and the PHA particles with a particle size of 180 nm obtained in Example 3 ([P(3HB-co-4HB)], 4HB repeating unit: 8.7 wt %, molecular weight: 390,000 g / mol) were dissolved (dispersed) in 0.1 M PBS buffer (pH 7.4) at concentrations of 30% (w / v), 50% (w / v) and 70% (w / v), respectively, to obtain compositions (PHA3 (4HB repeating unit: 17 wt %) and PHA4 (4HB repeating unit: 8.7 wt %)), and their antibacterial activities were evaluated, respectively. The results are shown in FIG. Fig.21 Specifically, when the OD 600 value reached 0.5, each PHA composition was added to 0.2 ml of Escherichia coli (E. coli) solution, which was then applied to LB solid medium. Subsequently, after incubation at 37°C for 12 hours, the colony formation degree of E. coli was analyzed by measuring the number of colonies formed.

[0222] refer to Fig.21 , the colony counts of the medical compositions (PHA3 and PHA4) according to the present disclosure decreased with increasing PHA concentrations. These results support that the medical composition (bacterial infection inhibition composition) according to the present disclosure has an efficacy in inhibiting bacterial infection.

Claims

1. A medical composition comprising a polyhydroxyalkanoate (PHA) having a particle size of 10,000 nm or less and comprising a repeating unit derived from 3-hydroxybutyrate (3HB) in an amount of 40 wt% or more based on the total weight. 2 . The medical composition according to claim 1 , which has a tissue adhesive strength of 15 kPa or more when measured at a relative humidity of 100% and room temperature.

3. The medical composition according to claim 1, wherein the polyhydroxyalkanoate (PHA) further comprises a repeating unit derived from 4-hydroxybutyrate (4HB). 4 . The medical composition according to claim 3 , wherein the content of the repeating unit derived from 4-hydroxybutyrate (4HB) is 0.1 to 60 wt % based on the total weight of the polyhydroxyalkanoate (PHA).

5. The medical composition according to claim 1, wherein the polyhydroxyalkanoate (PHA) is poly (3-hydroxybutyrate-co-4-hydroxybutyrate) copolymer.

6. The medical composition according to claim 1, wherein the molecular weight of the polyhydroxyalkanoate (PHA) is 10,000 to 1,200,000 g / mol.

7. The medical composition according to claim 1, wherein the concentration of the polyhydroxyalkanoate (PHA) is 0.1 to 75% (w / v).

8. The medical composition according to claim 1, which is used for hemostasis.

9. The medical composition according to claim 1, which is used for wound healing.

10. The medical composition according to claim 1, which is used for tissue adhesion.

11. The medical composition according to claim 1, which is used for inhibiting bacterial infection.

12. A method for preparing a medical composition, the method comprising: dissolving polyhydroxyalkanoate (PHA) in a solvent to prepare a dispersed phase solution; preparing a continuous phase solution comprising a surfactant; passing the dispersed phase solution through a membrane having a pore size of 10,000 nm or less to form an emulsion in which dispersed phase particles are dispersed in the continuous phase solution; and The emulsion is solidified to obtain polyhydroxyalkanoate (PHA) particles having a particle size of 10,000 nm or less. 13 . The method for preparing a medical composition according to claim 12 , wherein the content of polyhydroxyalkanoate (PHA) contained in the dispersed phase solution is 0.01 to 5 wt % based on the total weight of the dispersed phase solution.

14. The method for preparing a medical composition according to claim 12, wherein the dispersed phase solution passes through the membrane at a pressure of 2.5 to 320 kPa.

15. A method for preparing a medical composition, the method comprising: dissolving polyhydroxyalkanoate (PHA) in a solvent to prepare a dispersed phase solution; preparing a continuous phase solution comprising a surfactant; mixing the dispersed phase solution with the continuous phase solution to form a premixed emulsion; injecting the premixed emulsion into a high-pressure dispersion device (microfluidizer) to form an emulsion in which polyhydroxyalkanoate (PHA) particles having a particle size of 10,000 nm or less are dispersed; and The emulsion is solidified to obtain polyhydroxyalkanoate (PHA) particles.

16. The method for preparing a medical composition according to claim 15, wherein the pressure applied to the premixed emulsion by the high pressure dispersing device is 1 to 30 kpsi.